Responses to Systemic Nitrogen Signaling in Arabidopsis Roots Involve trans-Zeatin in Shoots. Issue 6 (15th May 2018) - Poitout, Arthur; Crabos, Amandine; Petřík, Ivan; Novák, Ondrej; Krouk, Gabriel; Lacombe, Benoît; Ruffel, Sandrine
Abstract : The level of the cytokinin trans -zeatin in shoots controls the molecular, physiological, and growth responses of nitrate-supplied roots in a root system facing heterogeneous nitrate availability. Abstract: Plants face temporal and spatial variation in nitrogen (N) availability. This includes heterogeneity in soil nitrate (NO3   − ) content. To overcome these constraints, plants modify their gene expression and physiological processes to optimize N acquisition. This plasticity relies on a complex long-distance root-shoot-root signaling network that remains poorly understood. We previously showed that cytokinin (CK) biosynthesis is required to trigger systemic N signaling. Here, we performed split-root experiments and used a combination of CK-related mutant analyses, hormone profiling, transcriptomic analysis, NO3   − uptake assays, and root growth measurements to gain insight into systemic N signaling in Arabidopsis thaliana . By comparing wild-type plants and mutants affected in CK biosynthesis and ABCG14-dependent root-to-shoot translocation of CK, we revealed an important role for active trans -zeatin ( t Z) in systemic N signaling. Both rapid sentinel gene regulation and long-term functional acclimation to heterogeneous NO3   − supply, including NO3   − transport and root growth regulation, are likely mediated by the integration of tZ content in shoots. Furthermore, shoot transcriptome profiling revealed that glutamate/glutamine metabolism is likely a target of t Z root-to-shoot translocation, prompting an interesting hypothesis regarding shoot-to-root communication. Finally, this study highlights t Z-independent pathways regulating gene expression in shoots as well as NO3   − uptake activity in response to total N deprivation.